Genetic Variation of VKORC1 and CYP4F2 Genes Related to Warfarin Maintenance Dose in Patients with Myocardial Infarction. (24th November 2010) - Kringen, Marianne K.; Haug, Kari Bente Foss; Grimholt, Runa M.; Stormo, Camilla; Narum, Sigrid; Opdal, Mimi S.; Fosen, Jan Toralf; Piehler, Armin P.; Johansen, Per W.; Seljeflot, Ingebjørg; Berg, Jens Petter; Brørs, Odd
Abstract : The aim of this study was to investigate whether the VKORC1 * 3 (rs7294/9041 G > A), VKORC1 * 4 (rs17708472/6009 C > T), and CYP4F2 (rs2108622/1347 C > T) polymorphisms were associated with elevated warfarin maintenance dose requirements in patients with myocardial infarction (n = 105 ) from the Warfarin Aspirin Reinfarction Study (WARIS-II). We found significant associations between elevated warfarin dose requirements and VKORC1 * 3 and VKORC1 * 4 polymorphisms (P = .001 and P = .004, resp.), whereas CYP4F2 (1347 C > T) showed a weak association on higher warfarin dose requirements (P = .09 ). However, analysing these variant alleles in a regression analysis together with our previously reported data on VKORC1 * 2, CYP2C9 * 2 and CYP2C9 * 3 polymorphisms, gave no significant associations for neither VKORC1 * 3, VKORC1 * 4 nor CYP4F2 (1347 C > T). In conclusion, in patients with myocardial infarction, the individual contribution to warfarin dose requirements from VKORC1 * 3, VKORC1 * 4, and CYP4F2 (1347 C > T) polymorphisms was negligible. Our results indicate that pharmacogenetic testing for VKORC1 * 2, CYP2C9 * 2 and CYP2C9 * 3 is more informative regarding warfarin dose requirements than testing for VKORC1 * 3, VKORC1 * 4, and CYP4F2 (1347 C > T) polymorphisms.